PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR PERKEMBANGAN MAKHUK HIDUP PADA SISWA KELAS IV SD PLUS AHMAD DAHLAN - Ai Siti Rosmawati; Esti Pramithasari; Ghina Amalia; Revina Ramadhani; Farraj Azman Muyasar; Rana Gustian Nugraha (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2026)
Students in the fourth grade of Ahmad Dahlan Plus Elementary School showed low levels of activity and learning outcomes in the subject of Living Things Development. This was due to a teacher-centered learning approach. The purpose of this study was to determine how the Discovery Learning model affected students’ science learning outcomes. A pre-experimental design was used, with a single group pretest-posttest design. A saturated sample method was used to examine 8 selected fourth-grade students. Learning outcome tests were conducted before and after the treatment. The Shapiro–Wilk normality test, paired sample t-test, and descriptive statistics were used to analyze the data. The results showed a significant difference between the pretest and posttest scores; the average score increased from 78.75 on the pretest to 95.00 on the posttest (p < 0.05). These findings indicate that using the Discovery Learning model significantly improves student learning outcomes in the subject. This model increases student activity, improves their understanding of ideas, and creates more meaningful learning for them.